Healthcare information technology (IT) and management systems Part 4 – suggestions for solutions in Poland for Patient Internet Account - Wdowiak, Leszek; Horoch, Andrzej; Bojar, Iwona (Polish Journal of Public Health, 2009)
Basing on national and foreign experiences and by analysing the ways in which the projects were developed in other European countries to offer patients Internet Account as well as the functionality of the account, one can notice the regularity that the evolutionary approach to information technology issue in health care, is most effective. When subsequent functionalities are implemented in stages, starting from the simplest accessible then possibilities, next they allow for launching of new services and building up the system. In Poland there is an effectively functioning National Health Care System –OSOZ, which successfully realizes nowadays the functionality of patient internet account on the level permitted by Polish law. Complete functionality of the Patient Internet Account due to legislative reasons, is not possible at this stage in any of the systems. The present article is presenting the assumptions for further studies concerning the implementation of information technology system in health care in Poland.The project recommends the use of National Health Care System – OSOZ- as the solution that is best adapted to the currently functioning legal acts. This solution in the present form practically implements the best practices encountered in foreign projects with the proved functional effects. The solution implemented deliberately and systematically, with the support of health care decision-makers, has great chances to be one of the most comprehensive systems of this type in Europe.